Monocyte Activation Test (MAT) as a possibility of replacement for the rabbit pyrogen test in hyperimmune sera - Carla Lilian de Agostini Utescher; Klariane Laís Buosi; Viviane Fungaro Botosso; Wagner Quintilio (Universidade de São Paulo, 2018)
ABSTRACT The use of a commercial kit for the monocyte-activation test (MAT) was evaluated for assessing pyrogenic contamination of hyperimmune sera . Three batches of sera, two pyrogen free and one pyrogenic, were tested. Endotoxin spike recover indicated that sample dilutions from 1/2 to 1/10 are suitable. Kit transport and storage conditions were also evaluated, proving that an adequate cold chain must be assured to achieve good results. Furthermore, the commercial MAT kit seemed suitable to replace the rabbit pyrogen test (RPT) for pyrogen testing of hyperimmune sera, although further tests are needed to a full validation.